A Study on the Effects of Air-terminal Shape to Performance of Air-terminal - น้ำหอมจันทร์, ธนากร; เสรีพัฒนานนท์, อติกร; คชภูมิ, พงษ์สวัสดิ์ (Frontiers in Engineering Innovation Research, 2010)
This paper presents the study on the effects of air-terminal shape to performance of air-terminal. The air-terminal used in the experiments has 5 shapes and simulate earth resistance in range 0-5 ohms. The experiments and measurement use negative polarity DC high voltage test according to IEC 60060-1, IEC 60060-2 and IEEE 4-1995 standards. The test results show the earth resistances are increase 1 ohm the performance of (a) sharp, (b) blunt, (c) cone, (d) round shape and (e) multi point air terminal shape are decrease in 0.11-0.27, 0.10-1.10, 0.29-1.30, 1.08-5.36 and 0.33-l.56 percent respectively.